Calibração e validação de modelos de meso e microssimulação do tráfego para a avaliação de intervenções tático-operacionais na malha viária urbana - Maia, Felipe Viana Bezerra (2007)
The modeling of the traffic flow on the urban road infrastructure have become one of the most important tools to analyze the performance of new strategies and policies of traffic control aimed at improving the efficiency of the transportation system. However, to model the traffic flow in a solid way it is essential that the stages of calibration and validation of the simulation model are satisfactorily accomplished. This work presents a procedure, with an eminently practical focus, for the calibration and validation of simulation models to analyze tactical and operational interventions in the urban road network. This procedure comprises the following stages: i) definition of the road network to be modeled; ii) selection of the simulation model; iii) definition of the simulation network; and iv) calibration and validation of the simulation model. After specifying the tasks necessary to develop each one of these stages, this procedure was applied in an area of the city of Fortaleza-Ceará, using a traffic microsimulation software (INTEGRATION) and a mesosimulation package (TransCAD), to compare the calibration processes in each one, emphasizing their specificities. Nowadays, the use of traffic simulation models is not very spread in the Brazilian technical community and there are no calibration and validation procedures to facilitate the use of these programs. The author hopes that the procedure proposed in this research, as well as the discussions about its application, help to diffuse the use of traffic simulation to support the evaluation of interventions that provide a better use of the actual transportation infrastructure.